Uma formulação variacional do tipo mínimos quadrados para equações diferenciais ordinárias aplicável ao tratamento numérico de problemas de controle ótimo - Telma Cristina Pimenta de Freitas (1996)
The equivalence between an initial value problem described by ordinary differential equations and the extremum of a least square type functional is showed to happen under certain regularity condition hypothesis. This allows the formulation of a numerical procedure for optimal control problems with control discontinuites. This procedure is based on the substitution of differential constraints of the optimal control problems by a accessory variational problem. The construction of the least square functional can be interpreted as an exactly penalization technique for the differential constraints creating a natural means for the Ritz Method application on the differential equations that are present on the optimal control problems. The procedure is illustrated by mean of numerically solved examples.